2005
DOI: 10.1016/j.euje.2004.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Multicentric familial cardiac myxoma

Abstract: Familial cardiac myxoma is a rare syndrome which constitutes approximately 10% or less of all myxomas. We describe a rare case of LA and LV mass simultaneously in a 35-year-old female presenting to our hospital for evaluation of recurrent cardiac myxoma. Echocardiography revealed both LA and LV mass. Surgery was done and histological findings confirmed the diagnosis of myxoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Syndrome myxoma or Carney’s syndrome also consists of extracardiac myxomas in the breast or skin, spotty pigmentation, and endocrine overactivity. Patients with Carney’s syndrome are often younger (20 years old) and the cardiac myxomas are usually multiple and recurrent, involving more than 1 cardiac chamber and unusual locations ( 20 , 21 ). Familial cardiac myxomas appear to have an autosomal dominant transmission.…”
Section: Special Patient Populationsmentioning
confidence: 99%
“…Syndrome myxoma or Carney’s syndrome also consists of extracardiac myxomas in the breast or skin, spotty pigmentation, and endocrine overactivity. Patients with Carney’s syndrome are often younger (20 years old) and the cardiac myxomas are usually multiple and recurrent, involving more than 1 cardiac chamber and unusual locations ( 20 , 21 ). Familial cardiac myxomas appear to have an autosomal dominant transmission.…”
Section: Special Patient Populationsmentioning
confidence: 99%
“…Myxoma may present with many clinical syndromes such as neurological events and PTE. It was reported that about 20-30% of patients with atrial myxoma had neurological complications [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18].…”
Section: Discussionmentioning
confidence: 99%
“…The CNS events include progressive headache, nausea or vomiting due to the increase of intracranial pressure, limbs or body weakness or numbness and new onset of seizure [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 2 ] Familial multicentric cardiac myxomas may present as a case of left atrial (LA) and left ventricular (LV) mass simultaneously. [ 3 ]…”
Section: Introductionmentioning
confidence: 99%